2007
DOI: 10.2460/javma.231.8.1225
|View full text |Cite
|
Sign up to set email alerts
|

Management and complications of anesthesia for transvenous electrical cardioversion of atrial fibrillation in horses: 62 cases (2002–2006)

Abstract: Short-duration anesthesia for TVEC of atrial fibrillation in horses without underlying cardiac disease was a safe procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…In the present study, mean HR was 34 ± 6 beats per minute and SI, CI and ABP were within the normal ranges reported for healthy, isoflurane anaesthetized horses. These results agree with the findings of Bellei et al. (2007), who reported that perianaesthetic complications and overall cardiovascular data of 62 horses anaesthetized for TVEC and of 60 healthy horses anaesthetized for magnetic resonance imaging were comparable.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, mean HR was 34 ± 6 beats per minute and SI, CI and ABP were within the normal ranges reported for healthy, isoflurane anaesthetized horses. These results agree with the findings of Bellei et al. (2007), who reported that perianaesthetic complications and overall cardiovascular data of 62 horses anaesthetized for TVEC and of 60 healthy horses anaesthetized for magnetic resonance imaging were comparable.…”
Section: Discussionsupporting
confidence: 92%
“…Peri‐ and post‐operative pain relief, in the present study, was provided by administration of flunixin meglumine for 2–3 days because a mild degree of muscle stiffness was observed in the first horses undergoing TVEC. Bellei et al. (2007) also reported that 7.9% of the horses undergoing TVEC had mild signs of possible post‐anaesthetic myopathy, characterized by mild to moderate tachycardia, stiffness of gait, discomfort, muscle swelling or lameness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations